High‐dose statin therapy and risk of intracerebral hemorrhage: a meta‐analysis. (9th December 2015) - Pandit, A. K.; Kumar, P.; Kumar, A.; Chakravarty, K.; Misra, S.; Prasad, K.
Abstract : Statin plays a major role in the primary and secondary prevention of cardiovascular disease (CVD). Inconsistent findings in the studies have been observed toward the risk of intracerebral hemorrhage (ICH) using higher dose of statin. To examine this issue, we performed a meta‐analysis of randomized controlled trials (RCTs) to assess the association between higher dose of various statins and risk of ICH among patients with CVD. Literature was searched for studies published before June 10, 2015, using electronic database 'PubMed', 'EMBASE', and 'Google Scholar' as well as from many trial databases. The following search terms were used: 'Statin therapy' AND 'Cardiovascular Disease', AND 'Dose' AND 'Intracerebral hemorrhage', AND 'Randomized Controlled Trials' AND 'High Dose Statin'. High dose of statins was defined as atorvastatin 80 mg, simvastatin 80 mg, pravastatin 40 mg, rosuvastatin 20 mg per day. Fixed‐effect model was used to estimate the risk ratio (RR) and 95% confidence interval (CI) if heterogeneity was <50%; otherwise, random‐effect model was used. Begg's funnel plot was used to assess the publication bias. Seven RCTs involving 31, 099 subjects receiving high‐dose statin and 31, 105 subjects receiving placebo were analyzed in our meta‐analysis. A significant risk of ICH was observed in subjects with higher dose of statin (RR = 1.53; 95% CI: 1.16–2.01; P = 0.002). There was no difference in all‐cause mortality between the two groups (RR = 0.95; 95% CI: 0.86–1.06; P = 0.36). No publication bias was observed through Begg's funnel plot. Higher dose of statins was found to be associated with the risk of ICH. Future studies are needed to confirm these findings.